Head and neck squamous cell carcinoma in pregnant women1. Issue 3 (16th March 2012) - Eliassen, Anna M.; Hauff, Samantha J.; Tang, Alice L.; Thomas, Dafydd H.; McHugh, Jonathan B.; Walline, Heather M.; Stoerker, Jay; Maxwell, Jessica H.; Worden, Francis P.; Eisbruch, Avraham; Czerwinski, Michael J.; Papagerakis, Silvana M.; et al.
Abstract Background The aim of this study was to investigate oral cancer in pregnant women, a rare but therapeutically challenging patient subset. Methods After institutional review board approval, an EMERSE search was used to identify all women treated at the University of Michigan from 1998 to 2010 with head and neck squamous cell carcinoma (HNSCC) during pregnancy. This identified 4 patients with tongue cancer. Biomarkers and human papillomavirus (HPV) were assessed by immunohistochemistry and multiplex PCR/mass spectrometry, respectively. Results Two patients responded well to therapy and are alive more than 10 years after diagnosis; 2 patients died of disease. All tumors overexpressed EGFR and Bcl‐xL, 3 of 4 overexpressed c‐Met, both tumors that progressed overexpressed p53. All tumors were negative for HPV, p16, estrogen receptor, progesterone receptor, and HER‐2. Conclusions Biomarkers of aggressive tumors (high EGFR, c‐Met; high Bcl‐xL‐low p53) did not correlate with outcome. Additional studies are needed to determine whether perineural invasion, delay in diagnosis, and p53 overexpression are factors in poor survival. © 2012 Wiley Periodicals, Inc. Head Neck, 2013